Smart Cane: A Low Cost Assistive Device for the Visually Impaired - Kazi, Wohiduzzaman; Limu, Taslima Jannat; Md. Rakibuzzaman (EAI Endorsed Transactions on Internet of Things, 2023)
Vision impairment or low vision is the disability to see any objects clearly. It might be caused by old age, an accident, or any other neurological condition. People find it difficult to carry out their regular activities, regardless of the cause of their vision impairment or blindness. As medical researchers are working to find a cure for blindness, contrariwise researchers are using technology to make a vision impairment person’s life easier in an affordable way. As a result, a smart cane was developed, although it is expensive for most of blind people. The main objective of this paper is to introduce an affordable smart cane for every visually impaired person. The ultrasonic sensors in this walking stick are used to identify impediments. This system is using an arduino to reduce the processing time between receiving and delivering signals created by ultrasonic sensors. The speech output will guide a blind person to take a safe path making the stroll more comfortable and secure.